The correlation between serum cytokine levels and liver cirrhosis in chronic hepatitis B patients: A meta-analysis - Gaofeng Cai; Zhengting Wang; Jun Yao; Kui Liu; Zhifang Wang; Yongdi Chen; Huakun Lv; Biao Zhou; Chonggao Hu (Archives of Hepatitis Research - Peertechz Publications, 2018)
Background: The harm of liver cirrhosis (LC) is serious, and the development of LC is primarily resulted from chronic hepatitis B virus (HBV) in high-risk such as China and Africa and chronic hepatitis C virus (HCV) in developed areas such as United States. Currently, there were 360 million chronic HBV-infected people on a global scale, and 30 million chronic hepatitis B (CHB) patients in China. In general, cytokines can regulate immune responses or contribute to deleterious tissue injury. However, the effects of these cytokines reported were controversial. Therefore, we executed a meta-analysis evaluating whether these cytokines can change the development risk of LC.  Methods: CHB patients were taken as participants, and studies were searched from Springer, Wiley, Chinese Medical Journal Database, PubMed, Elsevier, OVID, EBSCO, Mean difference (MD) with 95% confidence intervals (CI) were calculated by Review Manager 5.1. Results: In this meta-analysis, 731cases and 1012 controls from 30 studies were analyzed. The pooled MD of the serum cytokines were transforming growth factor-β1 (TGF-β1): 25.86 (95% CI : 184.73-286.99)pg/ml, interleukin(IL)-6: 56.35 (95% CI : 19.00-93.70) pg/ml, IL-17:22.07(95% CI : 11.77-32.37) pg/ml, IL-10:-3.24 (95% CI : -4.11, -2.36) pg/ml, and interferon-γ (IFN-γ): 1.50(95% CI : -4.34-7.35) pg/ml, respectively. Discussion: In CHB patients, elevated of serum levels for TGF-β, IL-6, and IL-17 can increase the risk of LC development, whereas elevated of serum levels for IL-10 decreased the risk. We suggest high-risk subjects with elevated of serum levels for these cytokines should be closely monitored and receive treatment timely for reducing the development of LC.